The Transition to College: an Acculturation Comparison of Domestic and International Students - (:unkn) unknown (My University, 2014)
Domestic and international students face challenges when transitioning to college. Researchers believe first-year intervention programs and orientation are important in successful transition to the university environment. Student involvement from the beginning of the first semester helps create a connection to college and a sense of belonging. Domestic and international students traverse homesickness, financial issues, lack of social support, changes in routine, and academic issues while navigating life away from home. Additionally, students experience a turning point that can often create a change in educational trajectory that results in continuing in college, transferring out, dropping out, or seeking help. The turning point can be a part of collegiate culture shock that students experience during the acculturation process. Schlossberg's Transition Model (1981) serves as a foundation for how students adapt to change in college. The current research study investigates the resources used by first-year students to navigate the on campus journey as well as factors that affect college students' adjustment to campus. Results indicate students use the library, academic advising, computer labs, the on-campus gym, and financial aid. A sense of belonging at the institution and social connections on campus are two elements that help students make it past a turning point and continue academically. Results additionally found that domestic and international students from outside of the institution's area experience more collegiate culture shock than students originally from the suburbs of the institution's perimeter. Implications are discussed, and recommendations for future research are offered regarding the transition to college.
Keywords: Acculturation; Collegiate Culture Shock; First-year Students; International Students; Transition to College; Turning Point